2021
DOI: 10.3390/medicina57030218
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics of Long-Term Meditation Practice: Evidence for Prevention or Reversal of Stress Effects Harmful to Health

Abstract: Background and Objectives: Stress can overload adaptive mechanisms, leading to epigenetic effects harmful to health. Research on the reversal of these effects is in its infancy. Early results suggest some meditation techniques have health benefits that grow with repeated practice. This study focused on possible transcriptomic effects of 38 years of twice-daily Transcendental Meditation® (TM®) practice. Materials and Methods: First, using Illumina® BeadChip microarray technology, differences in global gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…A few studies examined neurotrophins[ 25 , 26 ]. Trans-criptomic analyses were performed in both healthy and clinical populations combining diverse MM activities in several longitudinal and mixed design studies and obtained similar results[ 24 , 27 - 29 ].…”
Section: Genetic Studies Of MMmentioning
confidence: 96%
See 2 more Smart Citations
“…A few studies examined neurotrophins[ 25 , 26 ]. Trans-criptomic analyses were performed in both healthy and clinical populations combining diverse MM activities in several longitudinal and mixed design studies and obtained similar results[ 24 , 27 - 29 ].…”
Section: Genetic Studies Of MMmentioning
confidence: 96%
“…Genetic studies of MM showed that differential transcription occurs in genes involved in DNA damage response, oxidative stress, and inflammatory metabolism processes, in both short and long-term practitioners[ 22 - 24 ]. In most studies, these results were correlated with reduced stress and fatigue, improved immune response, and clinical symptoms.…”
Section: Genetic Studies Of MMmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several critical observations and implications on the management of communicable and non-communicable diseases based on this series of papers. Using microarray experiments, Wenuganen et al studied the effects of Transcendental Meditation (TM) practice on the expression of 200 genes [31]. Compared to control group, 49 inflammation related genes were downregulated, while genes associated with antiviral and antibody components of the defense response were upregulated.…”
Section: Current Contributionsmentioning
confidence: 99%
“…In the second, a larger number of studies have reported associations between the twice-daily practice of TM and benefits for individual and collective health [see e.g., ( Schneider et al, 2012 ; Paul-Labrador et al, 2006 ; Orme-Johnson, 1987 ; Dillbeck and Cavanaugh, 2023 )]. The current secondary analysis of data from a previous report ( Wenuganen et al, 2021 ) concerns a less-pursued but important topic in research, namely, the search for biological mechanisms capable of supporting the reported health and wellbeing benefits of the practice.…”
Section: Introductionmentioning
confidence: 99%